The complete book of hummingbirds - Tilford, Tony (Thunder Bay Press, 2008)
"Named for the soft hum produced by their tiny wings that beat up to 200 times per second, hummingbirds are the smallest birds in the world and certainly among the most exquisite. The sight of these vivid creatures hovering before a flower or catching a ray of sunlight can be spellbinding. Often called "jewels in flight" for their iridescent colors, a list of common hummingbird names reads like a catalog of precious metals and gemstones." "The Complete Book of Hummingbirds is a comprehensive guide to these creatures that are found only in the Americas. This book features amazing close-up pictures from the collections of some of the world's foremost hummingbird photographers. It discusses hummingbirds' extraordinary biology, migration patterns, breeding and life cycles, and also gives suggestions on how hummingbirds can be attracted into the reader's backyard." "Along with a gallery of hummingbirds that provides key identification details, The Complete Book of Hummingbirds is as fascinating as it is beautiful."--Jacket.